Microbial Competition in the Subpolar Southern Ocean: An Fe–C Co-limitation Experiment - Fourquez, Marion; Bressac, Matthieu; Deppeler, Stacy L.; Ellwood, Michael; Obernosterer, Ingrid; Trull, Thomas W.; Boyd, Philip W. (Frontiers in Marine Science, 2020)
Iron (Fe) is a paradox in the modern ocean—it is central to many life-critical enzymes but is scarce across most surface waters. The high cellular demand and low bioavailability of Fe likely puts selective pressure on marine microorganisms. Previous observations suggest that heterotrophic bacteria are outcompeted by small diatoms for Fe supply in the SubAntarctic Zone of Southern Ocean, thereby challenging the idea of heterotrophic bacteria being more competitive than phytoplankton in the access to this trace metal. To test this hypothesis, incubation experiments were carried out at the Southern Ocean Time Series site (Mar.–Apr. 2016). We investigated (a) whether dissolved organic carbon (DOC), dissolved Fe, or both limit the growth of heterotrophic bacteria and, (b) if the presence of potential competitors has consequences on the bacterial Fe acquisition. We observed a pronounced increase in both bulk and cell-specific bacterial production in response to single (+C) and combined (+Fe+C) additions, but no changes in these rates when only Fe was added (+Fe). Moreover, we found that +Fe+C additions promoted increases in cell-specific bacterial Fe uptake rates, and these increases were particularly pronounced (by 13-fold) when phytoplankton were excluded from the incubations. These results suggest that auto- and heterotrophs could compete for Fe when DOC limitation of bacterial growth is alleviated. These interactions between primary producers and nutrient-recyclers are unexpected drivers for the duration and magnitude of phytoplankton blooms in the Southern Ocean.